2011
DOI: 10.1007/s11998-011-9327-0
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion protection of AISI 316 stainless steel by ALD alumina/titania nanometric coatings

Abstract: Stainless steels are used today in a wide range of applications as a result of their combination of high corrosion resistance and good mechanical properties. In some applications, for example, temporary contact biomedical devices or solar water heaters, corrosion resistance may need further improvement, and surface coatings may be applied for enhanced protection. In this study, AISI 316 stainless steel samples with two different standard industrial finishes were coated using atomic layer deposition (ALD) of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 18 publications
(14 reference statements)
1
43
0
Order By: Relevance
“…It is very interesting to note that corrosion studies of coatings prepared by ALD-based technologies using electrochemical techniques are recent and the major part of these studies are on coatings obtained by thermal-ALD technology; only three are dedicated to coatings prepared by PVD + ALD (Marin et al, 2011;Shan et al, 2008a) and PEALE (Potts et al, 2011). In the past decade, several studies were conducted on the potential use of ALD for the corrosion protection of different metal alloys mainly using salt-spray tests and/or potentiodynamic polarization (PP) and electrochemical impedance spectroscopy (EIS) techniques in aggressive solutions.…”
Section: Corrosion Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…It is very interesting to note that corrosion studies of coatings prepared by ALD-based technologies using electrochemical techniques are recent and the major part of these studies are on coatings obtained by thermal-ALD technology; only three are dedicated to coatings prepared by PVD + ALD (Marin et al, 2011;Shan et al, 2008a) and PEALE (Potts et al, 2011). In the past decade, several studies were conducted on the potential use of ALD for the corrosion protection of different metal alloys mainly using salt-spray tests and/or potentiodynamic polarization (PP) and electrochemical impedance spectroscopy (EIS) techniques in aggressive solutions.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…A totally equivalent Table 1 Time-line of ALE/ALD technologies, coating development and properties. D í az et al, 2011a,b;Hoivik et al, 2003;Marin, Lanzutti, Guzman, & Fedrizzi, 2011;Shan, Hou, & Choy, 2008a,b;Tripp et al, 2006;Lu, Wang, Zang, & Li, 2007;Wang et al, 2010a,b. a Atomic layer evaporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature such methods as plasma detonation technique [10], arc-ion plating [11], sol-gel deposition [12][13], chemical conversion layers of cerium [14] and chromium [15], chemical vapor deposition (CVD) [16], high-velocity oxy-fuel spray [17], plasma-nitriding [18], atomic layer deposition (ALD) [19,20] and electrophoretic deposition (EPD) [21] are reported. Between them, EPD is a very promising method that allows deposition of high-quality coatings of various materials at room temperature in comparatively short time.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Shan et al [19] used TiO 2 ALD layers to protect an undefined stainless steel, obtaining only a limited effect. In 2011, Marin et al [20], Diaz et al [21] and Potts et al [22] clearly showed that the residual porosity of ALD layers decreases increasing the thickness of the layer, thus improving the protection of the substrate. In most cases [20][21][22] the nanometric ALD layers clearly showed a corrosion protection similar, if not superior to conventional protective techniques and thicker coatings, even if common industrial tests (salt spray) performed on Plasma Enhanced ALD by Potts et al [22] clearly showed a time-limited corrosion protection.…”
Section: Introductionmentioning
confidence: 99%